Pengaruh Ukuran Pemerintah Daerah, Leverage, Belanja Modal dan Dana Perimbangan Terhadap Kinerja Keuangan Pemerintah Daerah Kabupaten/Kota di Provinsi Sumatera Selatan - Rifdah Aisyah; Rosy Armaini; Yevi Dwitayanti (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2026)
This study aims to explore the impact of Local Government Size, Leverage, Capital Expenditure, and Balance Fund on the Financial Performance of Regency and City Governments within South Sumatra Province. The analysis is based on secondary data sourced from audit reports issued by the BPK RI.The study included all districts and cities within the province, employing a saturated sampling method. Data were gathered through documentation and analyzed using panel data regression techniques. The results revealed that Local Government Size significantly and positively affects financial performance, while Leverage also shows a positive association. In contrast, Capital Expenditure demonstrates no measurable influence, and Balance Fund exhibits a significant negative effect. Taken together, these four independent variables collectively contribute a meaningful impact on the financial performance of local government.